HUBUNGAN PENGETAHUAN IBU RUMAH TANGGA DENGAN SIKAP PENGELOLAAN SAMPAH DI DESA MUARA OPU BATANGTORU KABUPATEN TAPANULI SELATAN TAHUN 2016 - ., Suryati; Antoni, Adi (Universitas Aufa Royhan, 2018)
Waste (garbage) management that has long existed doess not yet meet the method and technique of environmental-based waste (garbage) management that it brings negative impact to the environmental and public health. The purpose of this study was to find out the relationship between the knowledge ofhousewife and the action of waste (garbage) management in Desa Muara Opu, Kecamatan Muara Batangtoru, Kabupaten Tapanuli Selatan. The research uses descriptivestudy of correlation which surveys or studies have attempted to explore how and why health phenomenon that happens. The population is all housewives in Desa Muara Opu Kecamatan Batangtoru Kabubapaten Tapanuli Selatan as many as 116 housewives. Samples were taken by simple random sampling that is by raffle. Data was collected by questionnaire. Data were analyzed by using Chi Square test. The results of this study demonstrate the knowledge Housewife on Waste Management majorities in enough categories, less that 17 (58.6%). The attitude of the housewife in the management of waste in Desa Muara Opu Kecamatan Batangtoru Kabupaten Tapanuli Selatan majority in the unfavorable category is 16 people (55.2%). The results of chi square analysis showsthat sig = 0.001 (p <0.05) means that the hypothesis is accepted which means no statistical relationship between knowledge housewife with attitudes of waste management in Desa Muara Opu Kecamatan Batangtoru Kabupaten Tapanuli Selatan in 2016. The conclusion drawn from the result of this study is that there is a statistically and significant relationship between the knowledge of the housewives and the action of waste (garbage) management in Desa Muara Opu, Kecamatan Muara Batangtoru, the Kabupaten Tapanuli Selatan in 2016